A new approach to the calculation of bond work index for finer samples. (1st May 2021) - Nikolić, Vladimir; Trumić, Milan
Highlights: The determination of the Bond work index (BWI) on finer samples. Accurate determination of the (BWI) is essential for the proper design plant. Suggested equation for determination BWI on finer samples. The error is smaller than 2.5%. Abstract: The Bond work index (BWI) is a well-known method used when selecting comminution equipment, to evaluate the grinding efficiency and to calculate the required grinding power. Although considered an industry standard, Bond did not fully define that procedure, and therefore significant discrepancies in test results can sometimes be obtained due to some undefined steps in the method. One of these cases is the initial sample size for grinding, why it must be the initial sample size of 3.35 mm, and whether it is possible to determine the BWI on samples of finer classes. In practice, it is possible to find materials whose size is finer than 3.35 mm. This paper examines the determination of the BWI on finer samples and proposes an equation for the determination of the BWI on finer samples.